Time-, Sex-, and Dose-Dependent Alterations of the Gut Microbiota by Consumption of Dietary Daikenchuto (TU-100). (22nd February 2018) - Miyoshi, Jun; Nobutani, Kentaro; Musch, Mark W.; Ringus, Daina L.; Hubert, Nathaniel A.; Yamamoto, Masahiro; Kase, Yoshio; Nishiyama, Mitsue; Chang, Eugene B.
Abstract : Medications or dietary components can affect both the host and the host's gut microbiota. Changes in the microbiota may influence medication efficacy and interactions. Daikenchuto (TU-100), a herbal medication, comprised of ginger, ginseng, and Japanese pepper, is widely used in Japanese traditional Kampo medicine for intestinal motility and postoperative paralytic ileus. We previously showed in mice that consumption of TU-100 for 4 weeks changed the gut microbiota and increased bioavailability of bacterial ginsenoside metabolites. Since TU-100 is prescribed in humans for months to years, we examined the time- and sex-dependent effects of TU-100 on mouse gut microbiota. Oral administration of 1.5% TU-100 for 24 weeks caused more pronounced changes in gut microbiota in female than in male mice. Changes in both sexes largely reverted to baseline upon TU-100 withdrawal. Effects were time and dose dependent. The microbial profiles reverted to baseline within 4 weeks after withdrawal of 0.75% TU-100 but were sustained after withdrawal of 3% TU-100. In summary, dietary TU-100 changed mouse microbiota in a time-, sex-, and dose-dependent manner. These findings may be taken into consideration when determining optimizing dose for conditions of human health and disease with the consideration of differences in composition and response of the human intestinal microbiota.